Evaluation of Dental Prosthesis Service Campaign for The Elderly to celebrate on the Auspicious Occasion of His Majesty the King's Eightieth Birthday Anniversary 5th December 2007 - ดาโลดม, สุปราณี; วีรชัย, นนทลี; เวชวิธี, วรางคนา; เจียรมณีโชติชัย, สุธา (Thai Dental Public Health Journal, 2008)
The purpose of this study was to evaluate the process and factors influenced on Dental Prosthesis Service Campaign including acrylic partial denture 16 teeth or more and complete denture for the elderly nation-wide. Data were collected by questionnaires and interviews that has been revised by experts and calibrated before used in 3 groups ; provider, provincial coordinator and elderly group who received denture from this project. 215 questionnaires, covering denture service system, was administered to providers who work in hospitals in 8 provinces that were randomly chose 2 from each of 4 parts of Thailand. 75 questionnaires that covering supportive system were distributed to 75 provincial coordinators and 66 were included in the study. In the elderly group, 50 persons at random in each 8 provinces as above and 442 persons were interviewed in issues related to denture service and denture effectiveness. Statistical analysis was performed by means of descriptive statistics including the qualitative data from questionnaire and interview. This study indicated that 83.3% of the providers, 95.5% of the coordinated health personnel had the high level of satisfaction of this project and 93% of the elderly can use their dentures. Key success factors of this nation-wide project is Quality of the denture with corporation from Dental health personnel and other sectors within the government and non-governmental organization, Effective financial management, Being the project to celebrate His Majesty the King's Birthday anniversary, Being the policy that must be followed by Ministry of Public Health, and Having central organizing center. In addition, effective supportive system from the central ministry to all hospitals, effective report and data management, enhancing skill for dental professional, including continuous monitoring and evaluation must be involved in this project. Referral system and advisors for complicated cases,enhancing opportunity to access denture service and improving equality for denture service in all benefit package should be arranged to improve effectiveness and efficacy. Additional researches in oral health service needs for the elderly and impact of service to daily life and quality of life will be conducted along with Oral health service arrangement